Leitura elaborada: instrumento para a leitura em língua estrangeira? - Paula, Edetilde Mendes de (2006)
The main aim of this research is to make an analysis of the conception of reading implied in the German teacher s book of the Themen Aktuell s series, for German as a foreign language, particularly book number 1, in order to verify if the suggestions in this guide are pertinent to the texts and the recommended activities. Another aim is to analyze the type of information contained in this book. If we consider the importance of reading during the learning process of a foreign language, it becomes important to know not only the best conception of reading presented by this book, but also to analyze the explicit and implicit information in those texts specifically to develop the reading ability. This research does not have a direct interference on the observed object, because it has a documental basis and an interpretive character, seeking to analyze the concept of reading in this didactic book. This study is the result of some reflections on hypotheses elaborated by the researcher, in order to understand some questions, raised by her as a German teacher, related to reading and its conceptions. This way, this study s interpretations are marked for her subjectivity. The reflections on the raised hypotheses seem to demonstrate that the suggestions contained in the book Themen aktuell 1( teacher s manual) are insufficient for the development of the cognitives process and for the construction of meaning.